PENGARUH PEMAKAIAN EKSTRAK PEWRNA KULIT MANGGIS TERHADAP KUALITAS KUE MANGKOK - Fajriah, Irda Nelly; Yusuf, Liswarti; Kasmita, Kasmita (Journal of Home Economics and Tourism, 2013)
The purpose of this reseach is to analyze the influence of using extract mangosteen skin 5, 10, 15 cc to the quality of  shape, colour, texture, smell and taste from the cupcake and to find out the difference of influence from the use of skin extract 5, 10, 15 cc to the quality of  cupcake.This research is pure experiment research, the source of data in this research are 20 panelist who gave the answerrs from organoleptik test format. Data analysis has been done with data descriptive way. Then the collected research data will be analyzed using variant analysis (ANAVA) and continued with interpretation about the result of research data.Based on data analysis, it is proved that there is a significant influence in the quality of cupcake shape with  Fcount (49.537)  > Ftabel (2,72) that means there is the difference of significant influence. Quality color gained by Fcount (62.142)  < Ftabel (2,72) that means no significant influence towards the quality of color. Elastic Quality gained by Fcount (135.014) > Ftabel (2,72) which means there are significant influence towards the elastic texture qualiti of cupcake Keywords: kue mangkok, leather, ekstrak kulit manggis.